Über die Standortabhängigkeit des Massenwechsels der Lärchenminiermotte, Coleophora laricella Hb., und der Ahorneule, Acronycta aceris L. Ein Beitrag zur Entwicklung der vergleichend-biocönologischen Methode der Massenwechsel-Erforschung der Insekten. - Schwenke, Wolfgang (Contributions to Entomology = Beiträge zur Entomologie, 1958)
For the purpose of perfecting comparative-biocoenological researches on the natural control of insect populations the principles and terms of the comparative method are discussed. There are given results of an investigation concerning the population density and some of the factors controlling the densitiy of the Larch casebearer (Coleophora laricella Hb.) and the noctuid Acronycta aceris L. at different localities. Density and number of eggs of Coleophora laricella (examined near Berlin, Dessau and Leipzig) proved to depend on local types represented by vegetation. The differences of density within a given locality were caused by different intensity of light and wind. The density of Acronycta aceris was also dependent on local types in the city of Berlin (local type: chestnut tree in courtyard, - local type: chestnut tree in park). These differences were caused by the different way of cooperation of two factors: virosis and the parasitization of the larvae.